Occipital transtentorial approach for posterior cranial fossa lesions located away from the midsagittal plane: A technical note - Hideo Ohba; Toshiyuki Tsuboi; Yuko Miyazaki; Yosuke Kajihara; Shigeyuki Sakamoto; Kazutoshi Mukada; Shinji Ohba (World Neurosurgery: X, 2025)
Background: The occipital transtentorial approach (OTA) is a well-established technique for accessing lesions in the pineal region, posterior third ventricle, and dorsal midbrain. Compared to the supracerebellar infratentorial approach, OTA provides superior visualization without cerebellar obstruction. However, its application to posterior cranial fossa lesions located away from the midsagittal plane remains underexplored, and its lateral limitations have not been clearly defined. Case presentation: A 65-year-old woman with a symptomatic cerebellar tentorial meningioma located away from the midsagittal plane underwent tumor resection via OTA. A stepwise cerebrospinal fluid drainage strategy was employed to minimize brain retraction and optimize surgical exposure. The craniotomy extended across the superior sagittal and transverse sinuses to maximize visualization. The cranial limit was defined by the ascending vein joining the superior sagittal sinus, while the lateral limit was delineated by the confluence of the Vein of Labbé with the transverse sinus. No postoperative complications or permanent neurological deficits were observed. Discussion: A literature review revealed a lack of detailed reports on OTA for posterior fossa lesions located away from the midsagittal plane. We propose that the Vein of Labbé serves as a key anatomical landmark defining the lateral boundary of OTA. Embryological evidence further supports its validity as an anatomical constraint. Conclusion: This report provides a detailed description of OTA for posterior fossa lesions located away from the midsagittal plane. Our findings highlight the importance of the Vein of Labbé as a lateral boundary, necessitating further case accumulation and comparative studies to refine OTA indications.